Allegorical Language in the Holy Quran A Semiotic Interpretation of Surat Al-Hujurat - Ibrahim A. El-Hussari (Tafkir: Interdisciplinary Journal of Islamic Education, 2022)
Scholars, including both Muslim and non-Muslim philologists and anthropologists, tend to agree that the Muslim holy book, Al- Quran[1], is not an easy text to read, understand and interpret, much more so than any other holy text available, say The Torah or The Gospel. However, for an open-minded scholar, to interpret Al-Quran is to experience an either pleasant or unpleasant encounter with all that it holds. Hence the variety of textual analysis relative to the various levels of understanding of the original message embedded in the allegorical language shaping it. In this context, reading Al- Quran can be viewed as an exercise in semiotics. This paper presents a panoramic view of this holy Book, but it dwells, more particularly, on exploring the taxonomy of interpretation of the probable messages underlying chapter XLIX, Surat[2] “Al-Hujurat”[3]. Using a semiotic stance to touch upon some issues ingrained in the sign language of this specific text, this paper uncovers the composite fabric of the Muslim communal system which also sounds universal in application when it comes to the shaping of healthy communities as regards the issues of divinity, righteousness, faith, ethics, humanism, justice, and accountability.